2020
DOI: 10.1186/s40035-020-00196-0
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of vacuolar-type ATPase-dependent Lysosomal acidification in neurodegenerative diseases

Abstract: Background Lysosomes digest extracellular material from the endocytic pathway and intracellular material from the autophagic pathway. This process is performed by the resident hydrolytic enzymes activated by the highly acidic pH within the lysosomal lumen. Lysosome pH gradients are mainly maintained by the vacuolar (H+) ATPase (or V-ATPase), which pumps protons into lysosomal lumen by consuming ATP. Dysfunction of V-ATPase affects lysosomal acidification, which disrupts the clearance of substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 203 publications
6
94
1
Order By: Relevance
“…Genomic studies in mice and flies have shown that knockout of ATPase caused impaired presynaptic transmission, along with alterations in the amount and morphology of synapses [ 41 , 42 ]. These were important processes of V-ATPase deficiency contributing to cognitive impairment and neuronal degeneration [ 7 ], consistent with our findings of the participation of low ATP6V1A-mediated synaptic vesicle cycle in AD pathogenesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Genomic studies in mice and flies have shown that knockout of ATPase caused impaired presynaptic transmission, along with alterations in the amount and morphology of synapses [ 41 , 42 ]. These were important processes of V-ATPase deficiency contributing to cognitive impairment and neuronal degeneration [ 7 ], consistent with our findings of the participation of low ATP6V1A-mediated synaptic vesicle cycle in AD pathogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…This gradient of acidification is potentially mediated by vacuolar H + -ATPase (V-ATPase), a multisubunit enzyme consisting of V0 and V1 sectors that pumps protons into the lysosomal lumen by ATP consumption [ 6 ]. Dysfunction of V-ATPase-dependent acidification disrupts the trafficking of substrates between endolysosomal compartments, which may facilitate molecular steps for neuronal degeneration, such as AD [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our data provides further evidence for the importance of V-ATPase regulation for neurodevelopment. Moreover, our detection of cytosolic accumulation of potentially undegraded material in DEL neurons is consistent with similar examples of V-ATPase subunit disruption [ 59 , 60 ], supporting our findings that the absence of NCOA7 negatively affects lysosomal physiology. We did not, however, observe evidence for more overt lysosomal storage in primary neurons as has been described in other V-ATPase-associated mutant models [ 56 ].…”
Section: Discussionsupporting
confidence: 90%
“…Fig4-and Vac14-deficient mice show early neurodegeneration that has been attributed to defects in autophagy as well as the defective trafficking leading to vacuolation (Ferguson et al, 2009). Although complete loss of V-ATPase activity is lethal in mammals (Sun-Wada et al, 2000), compromised lysosomal acidification is associated with multiple neurodegenerative diseases and aging (Colacurcio and Nixon, 2016;Song et al, 2020). One form of Batten's disease arises from mutations in the CLN1 gene which compromise trafficking of the a1 subunit isoform and results in elevated lysosomal pH and severe neurodegeneration (Bagh et al, 2017).…”
Section: Neurodegenerationmentioning
confidence: 99%